Taklīf: Kerangka Teori Kalam Al-Qadi Abd Al-Jabbar - Matondang, H. Ali Yakub (Jurnal Usuluddin, 2004)
The concept of taklif according to al-Qadi Abd al-Jabbar, contained three principle aspects i.e. the essence of taklif God as Mukallif and maneis mukallaf. Al-Qadi Abd al-Jabbar uses these principles as a theory to build up his theological thought. In his view, there are two parts of taklif: the first is based on Divine Revelation called taklif sam i, and the second is based on reason called taklif aqli. On the Hereafter, God will question every single man and woman regarding the implementation of these taklif and He will give them reward or punishment accordingly.